Predictive value of serum HE4 and CA125 concentrations for lymphatic metastasis of endometrial cancer. Issue 1 (3rd November 2016) - Wang, Yingmei; Han, Cha; Teng, Fei; Bai, Zhaoyi; Tian, Wenyan; Xue, Fengxia
Abstract: Objective: To evaluate the predictive value of serum HE4 and CA125 concentrations in the preoperative prediction of risk of lymph node metastasis in endometrial cancer. Methods: A retrospective study was undertaken of data for patients with endometrial carcinoma treated surgically at a university hospital in China between August 2011 and December 2015. The preoperative serum levels of HE4 and CA125 were measured and analyzed by clinicopathologic characteristics. Results: Overall, 258 patients were included. The HE4 and CA125 concentrations were significantly elevated in patients with large lesions (≥2 cm), deep myometrial invasion (≥50%), an advanced disease stage, or lymph node metastasis ( P <0.05 for all). HE4 concentrations also rose with age and histologic grade ( P <0.01 for both). For lymph node metastasis, HE4 had higher sensitivity and negative predictive value than did CA125. The diagnostic performance of HE4 and CA125 in combination was superior to that of either marker alone. Conclusion: The combined evaluation of serum HE4 and CA125 could provide gynecologic oncologists with improved information to guide the decision of whether to perform lymphadenectomy. Abstract : The combined preoperative evaluation of serum HE4 and CA125 results in better prediction of lymphatic metastasis in endometrial cancer than evaluation of either measure alone.